RNA sequencing identifies a novel USP9X‐USP6 promoter swap gene fusion in a primary aneurysmal bone cyst. Issue 8 (6th March 2019) - Blackburn, Patrick R.; Davila, Jaime I.; Jackson, Rory A.; Fadra, Numrah; Atiq, Mazen A.; Pitel, Beth A.; Nair, Asha A.; VanDeWalker, Todd J.; Hessler, Mark G.; Hovel, Sara K.; Wehrs, Rebecca N.; Fritchie, Karen J.; et al.
Abstract: Primary aneurysmal bone cyst (ABC) is a benign multiloculated cystic lesion of bone that is defined cytogenetically by USP6 gene rearrangements. Rearrangements involving USP6 are promoter swaps, usually generated by fusion of the noncoding upstream exons of different partner genes with exon 1 or 2 of USP6, thus leading to transcriptional upregulation of full‐length USP6 coding sequence. Testing for USP6 rearrangements is used diagnostically to distinguish it from secondary ABC and other giant cell‐rich primary bone tumors. In this report, we present a case of a 16‐year‐old male with a primary ABC of the left distal femur. USP6 break apart fluorescence in situ hybridization was positive for a rearrangement and conventional chromosome analysis identified a reciprocal X;17 translocation. In order to identify the putative USP6 fusion partner, we performed RNA sequencing and uncovered a novel USP9X‐USP6 promoter swap fusion. This result was confirmed by reverse transcription‐polymerase chain reaction (RT‐PCR) and by mate pair sequencing thus showing the utility of these alternative methodologies in identifying novel fusion candidates. Ubiquitin‐specific protease 9X ( USP9X ), like USP6, encodes a highly conserved substrate‐specific deubiquitylating enzyme. USP9X is highly expressed in a number of tissue types and acts as both an oncogene and tumor suppressor in several human cancers. We conclude that oncogenic activation of USP6 via USP9X promoter exchange represents a novel driver of primary ABC formation.